DELORME PROCEDURE FOR FULL THICKNESS RECTAL PROLAPSE WITH COMPLETE FECAL INCONTINENCE: REPORT OF TWO CASES - Milev, Ilija; Mitevski, Aleksandar; Karagjozov, Panche (Journal of Morphological Sciences, 2022)
Complete rectal prolapse or procidentia is a protrusion of the rectum with all its layers trough the anus. The incidence ranges between 0.79-6.08 per 100 000. The diagnosis could be easily established on examination, or in cases with internal rectal prolapse by defecography. Weakness of the anal sphincters is very common with advance disease and approximately 50% to 75% of patients experience some form of fecal incontinence. Symptomatic rectal prolapse is an indication for operation. Over 100 operative procedures have been described for the treatment of rectal prolapse and they all can be categorized as transabdominal and transperineal procedures. Delorme procedure is a transperineal procedure that consists of resection a cylindrical mucosal flap and plication of the protruded rectal musculature. We are presenting two, old and debilitated patients with procidentia and complete fecal incontinence, successfully treated with Delorme procedure. The results of the treatment were remarkable regarding both the prolapse and the fecal incontinence. We are concluding that for the surgeon who is already familiar with other anorectal procedures, Delorme procedure is relatively simple and easy to learn, with excellent structural and functional results even in very poor risk patients with long segment rectal prolapse. Keywords: rectal prolapse, fecal incontinence, Delorme procedure.